2013
DOI: 10.1111/jmft.12062
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Family Therapists Working with Families in a Transitional Homeless Community

Abstract: The purpose of this study was to explore the experiences and observations of marriage and family therapists (MFTs) conducting an empirically supported parenting program at a transitional homeless community. A diary method was used in recording five MFTs' observations and reactions to implementing the psychoeducational groups. Fifty-one recordings were collected from three different parenting groups over the course of 20 weeks. Constant comparative method was used to identify themes related to MFTs' experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
(103 reference statements)
0
7
0
Order By: Relevance
“…This study is part of a larger trend to highlight non‐professional helping that occurs within social networks across a wide spectrum; for example, Harris‐McKoy, Woods, Brantley, and Farineau () found that homeless families supported one another in making the transition to gaining housing and other family issues. In the case of marriage and long‐term committed relationships, confiding relationship is ubiquitous, with people seeking support and input on problems ranging from everyday complaints to serious problems such as abuse and affairs.…”
Section: Resultsmentioning
confidence: 99%
“…This study is part of a larger trend to highlight non‐professional helping that occurs within social networks across a wide spectrum; for example, Harris‐McKoy, Woods, Brantley, and Farineau () found that homeless families supported one another in making the transition to gaining housing and other family issues. In the case of marriage and long‐term committed relationships, confiding relationship is ubiquitous, with people seeking support and input on problems ranging from everyday complaints to serious problems such as abuse and affairs.…”
Section: Resultsmentioning
confidence: 99%
“…When working with multistressed and multineed families, however, it is also important to consider the extent to which contextual factors might influence families' lives and our clinical work with them (Harris‐McKoy, Woods, Brantley, & Farineau, ). At‐risk families may be working to manage a number of stressors such as poverty, single‐parenthood, and employment challenges that may take precedence over content addressed in intervention efforts.…”
Section: Discussionmentioning
confidence: 99%
“…I said that I wanted to continue JMFT's commitment to the underserved and those in the margins. With this in mind, I am happy to see recent articles related to the treatment of the homeless (Harris‐McKoy, Woods, Brantley, & Farineau, ; Holtrop, McNeil, & McWey, ), those with physical and mental health issues (e.g., Houston‐Barrett & Wilson, ; MacPherson, Leffler, & Fristad, ; Wagner et al., ), those marginalized because of their sexual orientation, race, or other reasons (e.g., Coolhart, Baker, Farmer, Malaney, & Shipman, ; LaSala, ; Maciel & Knudson‐Martin, ; Quirk, Strokoff, Owen, France, & Bergen, ), those at risk for relational violence (Salis, Kliem, & O'Leary, ; Schneider & Brimhall, ; Taylor & Borduin, ), and substance abuse (e.g., Ladd & McCrady, ; Soloski, Kale Monk, & Durtschi, ). Similarly, we continue to publish important articles related to gender, power, culture, class, and their intersection (e.g., Knudson‐Martin et al., ; McDowell, Brown, Cullen, & Duyn, ; McDowell, Melendez‐Rhodes et al., ; Seedall, Holtrop, & Parra‐Cardona, ; Seshadri & Knudson‐Martin, ; Van Parys & Rober, ; Williams, Galick, Knudson‐Martin, & Huenergardt, ; Williams & Knudson‐Martin, ).…”
mentioning
confidence: 99%